(untitled) (Annals of Medical Research, 2022)
Aim: Hypoxemia due to obstructive sleep apnea (OSA) is thought to cause peripheral nerve damage. A case-control study was conducted to test the accuracy of this phenomenon. Materials and Methods: The patient group consisted of 45 patients with OSA who had an apnea-hypopnea index (AHI) score of >10 and were newly diagnosed with OSA and control group consisted of 37 individuals who did not have OSA. Sensory and motor nerve conduction investigations were performed on both the upper and right lower extremity Mann-Whitney U, chi square and independent sample T tests were carried out. Results: Both groups had the same average age of 46. The mean body mass index (BMI) in patients with OSA was 31.81; the average AHI was 55.17; the periodic leg movements in sleep (PLMS) was 30.71; the T90 value was 74.23; the lowest saturation was 37; the average saturation value was 72.97. The other nerves’ sensory and motor distal latency lengths were more prolonged than the control group, except the ulnar nerve. The averages of the left median, ulnar, and right peroneal motor nerves’ compound motor action potential (CMAP) amplitude were lower in individuals with OSA than in the control group. Compared to the control group, patients with OSA had slower right tibial nerve motor conduction velocity. The mean snap amplitude of bilateral median and left ulnar sensory nerve were higher in patients with OSA. Conclusion: OSA-induced hypoxia may have an impact on peripheral nerve damage.